Multidimensional Waveform Encoding: A New Digital Beamforming Technique for Synthetic Aperture Radar Remote Sensing - Krieger, Gerhard; Gebert, Nicolas; Moreira, Alberto (IEEE Transactions on Geoscience and Remote Sensing, 2008)
This paper introduces the innovative concept of multidimensional waveform encoding for spaceborne synthetic aperture radar (SAR). The combination of this technique with digital beamforming on receive enables a new generation of SAR systems with improved performance and flexible imaging capabilities. Examples are high-resolution wide-swath radar imaging with compact antennas, enhanced sensitivity for applications like alongtrack interferometry and moving object indication, and the implementation of hybrid SAR imaging modes that are well suited to satisfy hitherto incompatible user requirements. Implementationspecific issues are discussed and performance examples demonstrate the potential of the new technique for different remote sensing applications. © 2007 IEEE.
DLR Import::2019-04-02
Keywords: Adaptive radar; Along-track interferometry (ATI); Ambiguity reduction; Digital beamforming; Displaced phase centre antenna (DPCA); Ground moving target indication (GMTI); High-resolution wide-swath SAR imaging; Hybrid SAR; MIMO SAR